Analysis on cloud data service platform for digital oilfields - Zhu, Z.-P.; Pan, R.-F.; Chen, Z.; Li, G.-Q.; Zheng, G.-S. (Journal of Digital Information Management, 2016)

Augmented broadcaster identity-based broadcast encryption - Zhang, J.; Xu, Y.; Chen, Z. (Journal of Digital Information Management, 2013)
Identity-based Broadcast Encryption (IBBE) has the inherent key escrow problem that Private Key Generator (PKG) can fully determine the user's private key, which is an obstacle of the application of IBBE. The existing approaches to solving key escrow problem need the user to submit identity to multiple PKGs or interactions between PKG and the user in the private key extraction phase. For Point-to-Multipoint Identity-based Broadcast Encryption (P2MIBBE) that the computing capabilities of receiver are limited, these approaches are impracticable. We propose a new approach what we call Augmented Broadcaster Identity-based Broadcast Encryption (ABIBBE). It requires neither multiple PKGs nor calculation of receiver in the private key extraction phase. We construct a universal scheme to realize AB-IBBE, such that any IND-ID-CPA secure IBBE scheme can be extended to an IND-ID-CPA secure AB-IBBE scheme.
Keywords: Identity-based broadcast encryption; Key escrow